Snakebites in Domestic Animals - Andreia Garcês; Catarina Pereira; Maria Inês Santiago; Justina Prada; Filipe Silva; Isabel Pires (Biology and Life Sciences Forum)
In Portugal, there are four venomous species, the horned viper (Vipera latastei), seoane (Vipera seoanei), rat snake (Malpolon monspessulanus), and the hooded snake (Macroprotodon brevis ibericus), and in the UK, there is one: the common European adder (Vipera berus). Snake venom is a complex mixture of toxins whose composition varies depending on the family, genera, species, and even subspecies. In Europe, particularly Portugal, there are no published data on the frequency of these types of incidents, but it is estimated to be high, mainly in dogs. Thus, to characterize the injuries caused by the bite of venomous snakes in domestic animals, the authors describe cases in dogs, cats, and goats with a suspected snakebite. Animals presented wounds compatible with snakebites, with two points 1 to 1.8 cm apart that could be noted on the head or limbs. The main clinical signs observed included pain, oedema, and necrosis. From the animals that died, a post-mortem examination revealed subcutaneous and muscular necrosis and hemorrhages of surrounding tissues, including muscles and organic hemorrhages. The severity of envenomation depends on the quantity of inoculated venom; the species, age, size, and previous state of health of the bitten animal; the bite location; and post-bite excitability. With this study, the authors hope to help improve the knowledge regarding snakebites in Europe.